Novel THz Sources with Profiled Focusing Field and Photonic Crystal Electrodynamic Systems - Odarenko, E. N.; Shmat'ko, A. A. (IEEE, 2016)
Methods of the efficiency enhancement of the vacuum terahertz and subterahertz sources based on the resonance of O-type generators with a prolonged interaction (orotron, diffraction radiation oscillator, ledatron, laddertron) are considered. Theoretical analysis is performed on the basis of multidimensional nonlinear self-consistent theory of beam-wave interaction.
Keywords: Terahertz devices; nonlinear multidimensional theory; photonic crystal structures; profiled focusing field